Comparative Study of Serum Inflammatory Mediators and Immunoglobulin Levels in Children with Severe Bronchial Asthma Infected by Viruses Versus Bacteria - Zhang, Xiaoxia; Jian, Guojiang; Zhong, Xiaoqun; Li, Mao; Wan, Shifang; Liu, Huan; Chen, Xiangrui (Journal of Medical Biochemistry, 2025)
Objective: By tracking fluctuations in inflammatory mediators and immunoglobulins (Igs) in bacterial- versus viral-induced severe bronchial asthma (BA) cases, this research seeks to identify microbial-specific immune characteristics to guide individualized treatment. Methods: This analysis included 100 children hospitalized between March 2023 and April 2025 for severe acute BA exacerbations with confirmed single-pathogen infections (50 viral vs. 50 bacterial). Serum samples collected pre- and post-treatment were analyzed for inflammatory mediators (Th1/Th2/Th17 cytokines and TNF-α) and Ig profiles (total IgE and IgG subclasses). Comparative analysis was performed to identify intergroup differences. Results: At baseline, the viral group showed higher Th1/Th17 responses, whereas the bacterial group had elevated Th2 cytokines/TNF-α (P<0.05). Therapeutic intervention reduced all cytokine subsets, though Th1/Th17 suppression was more marked in the viral group (P<0.05), and Th2 decay lagged in the bacterial group. Besides, viral cases had elevated IgG1/IgG3; bacterial cases showed higher IgG2 (P<0.05). After treatment, the levels of IgG1 and IgG3 in the virus group continued to increase, but IgG2 did not change. Conclusion: Viral BA infections predominantly trigger Th1/Th17-mediated inflammation and higher IgG1/IgG3. In contrast, bacterial infections favor a Th2-dominant profile with IgG2 elevation, resulting in slower inflammation resolution.